Roman coinage and contemporary numismatic studies - Furlani, João Carlos (Romanitas - Revista de Estudos Grecolatinos, 2020)
Review of: KEMMERS, F. The functions and use of Roman coinage: an overview of 21st century scholarship. Leiden: Brill, 2019. 89 p.